An Evaluation of a Novel Method for the Detection of Parkinson's Disease - Meducator, The; Puusaari, Morgan; Shen, David (The Meducator, 2025)
Parkinson’s Disease (PD) is a neurodegenerative disorder affecting millions of individuals worldwide. However, current diagnostic tools are limited to the clinical assessment of overt symptoms, after PD has already progressed into the clinical stage. A novel PD testing method, α-synuclein seed amplification assay (αsyn-SAA), may revolutionize the testing by allowing clinicians to detect PD before symptoms arise. The α-synuclein protein abundant in pre-synapse is typically involved in the release of dopamine. However, in the development of PD, αsyn proteins become misfolded and infect their pathogenic conformations to other αsyn proteins through the prion-like process of seeding. αsyn-SAA testing identified PD progression by amplifying and measuring the accumulation of misfolded α-synuclein proteins in an individual’s cerebrospinal fluid. This critical review aims to appraise the mechanisms of αsyn-SAA testing, exploring its benefits and drawbacks. Notably, αsyn-SAA has been found to have over 90% sensitivity to PD and other synucleinopathies, while being able to distinguish between PD patients and healthy subjects with a high degree of accuracy. However, there are notable limitations and future longitudinal studies are necessary to optimize the specificity of αsyn-SAA testing.